Kinetic Study for Comprehensive Understanding of Solid-State Polymorphic Transitions of Nicotinamide/Pimelic Acid Cocrystals - Lee, Yong Joon; Pahom, Olga; Weeks, Brandon L (Crystal growth & design, 2019)
Solid-state polymorphic transition (SSPT) has been regarded as an interesting research subject for a long time, but kinetics and the mechanism of these phase transitions are still not fully understood. Particularly, kinetic studies on the SSPT process of cocrystals are not widely reported even though extensive novel cocrystal polymorphs have been discovered over the recent decades. Herein we presented a comprehensive kinetic study of the enantiotropic polymorphic system of 1:1 nicotinamide (NA)–pimelic acid (PA) cocrystals with the combination of various analytical methods. Bulk kinetic studies conducted with powder X-ray diffraction and differential scanning calorimetry indicated that both directions of SSPT (form 1 ↔ form 2) occur by a nucleation and growth mechanism. In addition, large activation energy barriers of form 1 → form 2 with a wide range (337.1–514.2 kJ mol–1) and variations in the onset transition temperature were observed, depending on the crystal conditions. In situ atomic force microscopy analysis was also carried out to monitor the surface morphology change at the nanoscale to supplement the bulk kinetics.